Audit on Naloxone Dispensing for Clients Prescribed Opioid Substitution Treatment (OST) in the CGL Service in East Sussex - Daniel Di Francesco (BJPsych Open, 2025)
Aims: To identify any patients on OST who have not been offered or received naloxone.